Prevalence of Cryptosporidium in La Trinidad, Benguet, Philippines: a One Health approach - Awisan, Jannette Depay; Rivera, Pilarita Tongol; Angeles, Jose Ma. Moncada (Frontiers in Parasitology, 2025)
IntroductionCryptosporidium species are zoonotic protozoa responsible for cryptosporidiosis, a serious public health concern for humans and animals. These protozoa are recognized for their capacity to infect various hosts, resulting in outbreaks that can cause significant health and economic consequences. The One Health approach considers human, animal, and environmental health interconnectedness and is vital in understanding and controlling the spread of such zoonotic diseases. This study adopts this approach to evaluate the prevalence of Cryptosporidium in humans, companion animals, livestock, and environmental water sources in La Trinidad, Benguet.MethodsA cross-sectional descriptive study was conducted from September 2020 to January 2022, adhering to research ethical standards approved by the Institutional Review Board (IRB) and following COVID-19 safety protocols such as social distancing, use of PPE, and regular sanitation of equipment and facilities. Stratified random sampling resulted in 314 participating households, which provided fecal samples from humans (up to two members), companion animals, and livestock. Samples were analyzed using microscopy (Sugar Flotation Technique, Formalin Ether Concentration Technique, and Kinyoun staining) and molecular methods, with genomic DNA extracted and nested PCR targeting the 18S rRNA gene. Water samples from 19 community sites underwent filtration and nested PCR analysis.ResultsFrom the 493 human, 363 animal, and 19 water samples analyzed, microscopic analysis revealed that 151 samples tested positive for Cryptosporidium oocysts, and molecular confirmation identified 135 (15.77%) as Cryptosporidium parvum. Livestock exhibited the highest prevalence (37.27%), followed by companion animals (18.58%) and humans (9.33%), indicating significant zoonotic transmission risks and highlighting the need for improved biosecurity measures. All water samples were negative.DiscussionThe high burden of Cryptosporidium in livestock presents significant risks for zoonotic transmission and reflects major shortcomings in biosecurity and sanitation. In contrast, the low human prevalence of COVID-19 suggests that enhancing hygiene practices combined with social restraint may help control infectious events. Further research is required to confirm this relationship. These results highlight the need for targeted public health interventions to reduce transmission risks.